Du keynésianisme au libertarianisme.La place de la monnaie dans les transformations du savoir économique autorisé - Bruno Théret (Revue de la Régulation)
This article looks for an understanding and explanation of the responsability of economics in the upsurge and development of the present crisis. It studies the interdependencies between the three streams of ideas which today dominate the departments of economics and finance of universities. Financial economics and « new classical » macroeconomics, combined with a renewal of « austrian » economics, form, thanks to their common reference to a libertarian ideology, an oligopoly which controls the new economic science that jointly with financial globalization has developped in the United States. As the paper starts from the evidence that the present crisis finds its origin at the monetary level, the analysis of this oligopoly is based on the place that money has in its three components. In Section I we justify this choice. Section II shows how money, whose characteristic is to have no economic role in General Equilibrium Theory, has tormented american mainstream economics since the nineteen seventies. Section III displays a topography of the field of economic ideas that allows to understand how the three libertarian streams of ideas, despite their large differences, were able to unite in order to form an hegemonic block and monopolize the production of authorized economic discourses. Final Section IV examines the paradox of a science that professes perfect self-regulation of markets and therefore its own uselessness, but in the same time has had an increasing role in the economic and political functionning of the present capitalist market economy.